Role of Colchicine in Reducing Reperfusion Injury in STEMI Patients Who Undergo Primary Percutaneous Coronary Intervention: A Randomized Clinical Trial - Birry Karim; Idrus Alwi; Mohammad Yamin; Merci Monica Pasaribu; Kuntjoro Harimurti; Nafrialdi Nafrialdi; Taufik Indrajaya; Rivaldo Rivaldo (Acta Medica Indonesiana)
Background: Inflammation plays a role in ST-segment elevation myocardial infarction (STEMI), especially in reperfusion injury (RI). Colchicine, an anti-inflammatory drug, can suppress inflammation during RI. We assessed the effectiveness of administering colchicine to STEMI patients undergoing primary percutaneous coronary intervention (PPCI) in suppressing RI events. Methods: This study was a randomized, double-blind, placebo-controlled clinical trial conducted in a multicenter manner at two hospitals in Jakarta with IKPP facilities from December 2022 to April 2023. STEMI patients that underwent PPCI received 2 mg of colchicine as a loading dose and a maintenance dose of 0.5 mg every 12 hours for two days or amylum at a similar dose. Patients were observed for RI events (low-flow thrombolysis in myocardial infarction (0–2) during angiography procedure, reperfusion arrhythmia, cardiogenic shock, or persistent chest pain). Results: Seventy-seven STEMI patients with a mean age of 55.2 ± 9.9 years underwent PPCI. Of these patients, 37 received colchicine, and 40 received a placebo. Most subjects were male (77.5%), suffered three-vessel disease (44.15%), and occlusion in left anterior descending coronary artery (53.24%). Colchicine was found to fail to reduce the incidence of ischemia-RI (51.5% vs. 42.4%; p = 0.437). Analysis of comorbidities (hypertension, chronic kidney disease, diabetes mellitus, and obesity) and angiography results (vessel disease, lesion diameter, and culprit artery) failed to demonstrate a statistical difference in RI. Side effects were similar in the colchicine and placebo groups (21.6% vs. 15%). Conclusion: Colchicine administration in STEMI patients undergoing PPCI failed to reduce RI.